Changes in Growth Parameter and Essential Oil Composition of Ajwain (Trachyspermum ammi) Fruits in Response to Various Biofertilizers: Pharmaceutical Science-Pharmacognosy - Jeet, Kamal; Baldi, Ashish (International Journal of Life Science and Pharma Research, 2022)
Unorganized natural nutrient cycle and depleted soil health may prove major limitation on the growth and development of medicinal plants and therefore quality and final yield of the cultivation. Therefore, studies concerned with the restoration of normal fertility to the soil and make it rich with certain nutrients are of the fundamental interest for medicinal plants. Herein, the present study was designed to investigate the multifaceted beneficial effects of (a) Phosphate solubilizing bacteria (Pseudomonas fluorescens) (b) Nitrogen-fixing bacteria (Azotobacter chroococcum) and (c) Mycorrhiza (Sebacina vermifera) on plant growth and seed essential oil composition of ajwain (Trachyspermum ammi). In this context, ajwain fruits were treated with selected biofertilizers to analyze the emergence pattern and to evaluate comprehensive growth and essential oil composition. About 25 days old seedlings were treated with selected biofertilizers. The results showed that all treatments had a good effect on seed emergence, though Sebacina vermifera assisted growth and essential oil production were much higher than other treatments. Concerning the composition, 13 compounds were identified using gas-chromatography. Major altered components were thymol, p-cymene and ϒ-terpinene. It is worthy to mention that each treatment proved to increase thymol only. The enhanced synthesis of thymol is supported by the speculation that biofertilizers may trigger an early or late step expression in biosynthetic pathway that leads higher production of thymol. As a conclusion, biofertilizers can alter the comprehensive growth including essential oil composition of ajwain, and also the chemical composition of ajwain was found to be strongly altered. Along with the study, Sebacina vermifera based biofertilizer indicated immense potentials to be utilize as multifaceted beneficial alternate for sustainable agronomical and medicinal plants productions.